Causal mechanisms of postnatal depression among women in Gondar town, Ethiopia: application of a stress-process model with generalized structural equation modeling - Abel Fekadu Dadi; Lillian Mwanri; Richard J. Woodman; Telake Azale; Emma R. Miller (BMC, 2020)
Abstract Background Postnatal depression (PND) is the second most common cause of disability and the most common complication after childbirth. Understanding the potential mechanisms by which the stress process can lead to PND is an important step for planning preventive interventions for PND. This study employed a stress process model to explore the possible pathways leading to PND in Gondar Town, Ethiopia. Methods A community-based cohort study was conducted in 916 pregnant women, who were assessed for depression in their second or third trimester of pregnancy and re-assessed two to eight weeks after birth. Women with an Edinburgh Postnatal Depression Scale (EPDS) ≥6 were considered to be depressed. Modified Poisson regression was used to identify the independent predictors of PND. A Generalized Structural Equation Modeling (GSEM) was then used to explore the direct and indirect effects of stressors and their mediators on PND. Results The prevalence and incidence proportion of PND were 9.27% (95%CI: 7.45, 11.36) and 7.77% (95%CI: 6.04, 9.79), respectively and 2.1% of the women demonstrated symptoms of depression within the study period. PND was independently predicted by having limited postnatal care services, Antenatal Depression (AND) and a Common Mental Disorders (CMD) before pregnancy, (IRR = 1.8; 95%CI: 1.0, 3.2), 1.6(95%CI: 1.4, 1.7), and 2.4 (95%CI: 1.4, 4.3) respectively). In SEM, AND (standardized total effect = 0.36) and a CMD before pregnancy (standardized total effect = 0.11) had both a direct and an indirect positive effect on PND scores. Low birth weight (standardized β = 0.32) and self-reported labor complications (standardized β = 0.09) had direct effects only on PND scores. Conclusion The observed incidence and prevalence of PND in Ethiopia were lower than in previous studies. A CMD before pregnancy and low birth weight (LBW) increased PND scores, and these effects were in part mediated via antenatal depression and labor complications. Early detection and treatment of depression before or during pregnancy could either directly or indirectly reduce the risk of labor complications and PND. Interventions that reduce LBW or improve the uptake of postnatal care might reduce PND incidence.